Pengaruh Islamic Corporate Governance Terhadap Tax Avoidance Pada Bank Umum Syariah Di Indonesia - Risqiyah, Metiya Fatikhatur; Pramuka, Bambang Agus (Media Ekonomi, 2021)
This research aimed to examine wether Islamic Corporate Governance proxied by the Sharia Supervisory Board, audit committee, proportion board of commissioners, profitabilitas and company size is able to minimize the tax avoidance of Islamic Banks in Indonesia. The sample of Islamic banks was used 11 Islamic Commercial Banks in the period 2015-2019. The sample was selected using a purposive sampling method. Multiple regression analysis is employed to test the hypotheses The results of this study show that sharia supervisory board, audit committee and proportion board of commissioner have a negative affect on tax avoidance, while profitability and company size have a possitive affect on tax avoidance.